Long-Term Safety and Efficacy of Abatacept in Children With Juvenile Idiopathic Arthritis - Ruperto, Nicolino; Lovell, Daniel J.; Quartier, Pierre; Paz, Eliana; Rubio-Perez, Nadina; Silva, Clovis A.; Abud-Mendoza, Carlos; Burgos-Vargas, Ruben; Gerloni, Valeria; Melo-Gomes, Jose A.; Saad-Magalhaes, Claudia [UNESP]; Chavez-Corrales, J.; et al. (Wiley-liss, 2010)
Objective. We previously documented that abatacept was effective and safe in patients with juvenile idiopathic arthritis (JIA) who had not previously achieved a satisfactory clinical response with disease-modifying antirheumatic drugs or tumor necrosis factor blockade. Here, we report results from the long-term extension (LTE) phase of that study.Methods. This report describes the long-term, open-label extension phase of a double-blind, randomized, controlled withdrawal trial in 190 patients with JIA ages 6-17 years. Children were treated with 10 mg/kg abatacept administered intravenously every 4 weeks, with or without methotrexate. Efficacy results were based on data derived from the 153 patients who entered the open-label LTE phase and reflect >= 21 months (589 days) of treatment. Safety results include all available open-label data as of May 7, 2008.Results. of the 190 enrolled patients, 153 entered the LTE. By day 589, 90%, 88%, 75%, 57%, and 39% of patients treated with abatacept during the double-blind and LTE phases achieved responses according to the American College of Rheumatology (ACR) Pediatric 30 (Pedi 30), Pedi 50, Pedi 70, Pedi 90, and Pedi 100 criteria for improvement, respectively. Similar response rates were observed by day 589 among patients previously treated with placebo. Among patients who had not achieved an ACR Pedi 30 response at the end of the open-label lead-in phase and who proceeded directly into the LTE, 73%, 64%, 46%, 18%, and 5% achieved ACR Pedi 30, Pedi 50, Pedi 70, Pedi 90, and Pedi 100 responses, respectively, by day 589 of the LTE. No cases of tuberculosis and no malignancies were reported during the LTE. Pneumonia developed in 3 patients, and multiple sclerosis developed in 1 patient.Conclusion. Abatacept provided clinically significant and durable efficacy in patients with JIA, including those who did not initially achieve an ACR Pedi 30 response during the initial 4-month open-label lead-in phase.